"The Feasibility of Targeted Muscle Reinnervation for the Management of Morton's Neuroma". Issue 1 (February 2022) - Kuruvilla, Shannon I.; Schaeffer, Christine V.; Cooper, Minton T.; DeGeorge, Brent R.
Background: Despite multiple surgical modalities available for the management of Morton's neuroma, complications remain common. Targeted muscle reinnervation (TMR) has yet to be explored as an option for the prevention of recurrence of Morton's neuroma. The purpose of the present investigation was to determine the consistency of the relevant foot neurovascular and muscle anatomy and to demonstrate the feasibility of TMR as an option for Morton's neuroma. Methods: The anatomy of 5 fresh-tissue donor cadaver feet was studied, including the course and location of the medial and lateral plantar nerves (MPNs and LPNs), motor branches to abductor hallucis (AH) and flexor digitorum brevis (FDB), as well as the course of sensory plantar digital nerves. Measurements for the locations of the muscular and sensory branches were taken relative to landmarks including the navicular tuberosity (NT), AH, FDB, and the third metatarsophalangeal joint (third MTPJ). Results: The mean number of nerve branches to FDB identified was 2. These branch points occurred at an average of 8.6 cm down the MPN or LPN, 9.0 cm from the third MTPJ, 3.0 cm distal to AH distal edge, and 4.8 cm from the NT. The mean number of nerves to AH was 2.2. These branch points occurred at an average of 6.3 cm down the MPN, 11.9 cm from the third MTPJ, 0.8 cm from the AH distal edge, and 3.8 cm from the NT. Conclusions: Recurrent interdigital neuroma, painful scar, and neuropathic pain are common complications of operative management for Morton's neuroma. Targeted muscle reinnervation is a technique that has demonstrated efficacy for the prevention and treatment of neuroma, neuropathic pain, and phantom limb pain in amputees. Herein, we have described the neuromuscular anatomy for the application of TMR for the management of Morton's neuroma. Target muscles, including the AH and FDB, have consistent innervation patterns in the foot, and consequently, TMR represents a viable option to consider for the management of recalcitrant Morton's neuroma. Levels of Evidence: V